EXTRACTIUON AND LYOPHILIZATION OF THE LOW DENSITY OF LIPOPROTEIN INSTEAD OF EGG YOLK ON SOME SEMEN PARAMETERS OF AWASSI RAMS - & Al-Saab, Al-Subaihawi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
This study was conducted  to explain the possibility of lyophilization of low– density lipoprotein (LDL)  that is extracted from the egg yolk to be used instead of the egg yolk in  an  extender semen that belong to the Awassi sheep and their effect on the characteristics of the semen after five days of cryopreservation, as well as to get low-density Lipoprotein, steriled and lyophilized (powder) lipoprotein that can be stored for a long time to used when needed. The study  was conducted in the from July 2015 to February  2016. The first stage started from July until  August 2015  the (LDL) was extracted from fresh egg. The second stage in August 2015. the liquid (LDL) has been lyophilized  and turn into powder that is packed in vials, steriled  vials  and then was stored in 0°C. The third stage was conducted from January to February 2016 in the college of Agriculture/ University of Baghdad. the semen was collected from four of the Awassi rams of the age (2– 4) years and the samples was collected by using  artificial vagina. After that the sample was divided on the experimental treatments evenly 1ml/ transaction by using extender Tris. The dilution ratio was 1: 10. The effect of the different concentrations had been studied of the LDL on the  characteristic of semen and three concentration of the LDL were used (3.2, 4.8 and 6.2%) for the transactions T1, T2,T3 respectively and the control treatment (20% EY).The effect of the lyophilized LDL was studied on some characteristic of sperm when cryopreserved under the temperature 5°c for five days. The Results of the experiment to varying differences between transactions in sperm characteristics as treatment outperformed T3 (P